LITERATURE REVIEW OF THE ETHNIC GROUP AFFILIATION AND L2 PROFICIENCY LINK: EMPERICAL EVIDENCE - Lina Farsia (CV Naskah Aceh, 2022)
There are many factors affecting in a second language (L2) Proficicency. In this literarure review, one of the factors that was examined is the ethic group affiliation. Ethnic group affiliation and L2 proficiency